GRP78/BiP determines senescence evasion cell fate after cisplatin-based chemotherapy - Zin Zin Ei (2022)
Cisplatin (CDDP) induces senescence characterized by senescence-associated secretory phenotypes (SASP) and the unfolded protein response (UPR). In this study, we investigated the proteins related to the UPR during the senescence cell fate. Strikingly, we found that one of the critical ER-resident proteins, GRP78/BiP, was significantly altered. Here we show that GRP78 levels differentially expressed depending on non-small lung cancer subtypes. GRP78 indeed regulates the evasion of senescence in adenocarcinoma A549 cells, in which the increased GRP78 levels enable them to re-proliferate after CDDP removal. Conversely, GRP78 is downregulated in the senescence H460 cells, making them lacking senescence evasion capability. We observed that the translational regulation critically contributed to the GRP78 protein levels in CDDP-induces senescence. Furthermore, the increased GRP78 level during senescence confers resistance to senolytic drug, Bortezomib, as observed by a twofold increase in IC50 in A549 senescence cells compared to the wild-type. This observation is also consistent in the cells that have undergone genetic manipulation by transfection with pcDNA3.1(+)-GRP78/BiP plasmids and pSpCas9(BB)-2A-Puro containing guide RNA sequence targeting GRP78 exon 3 to induce the overexpression and downregulation of GRP78 in H460 cells, respectively. Our findings reveal a unique role of GRP78 on the senescence evasion cell fate and senolytic drug resistance after cisplatin-based chemotherapy.